The Impact of Assertive Community Treatment on Utilization of Primary Care and Other Outpatient Health Services: The North Carolina Experience. (July 2013) - Wiley-Exley, Elizabeth; Domino, Marisa Elena; Ricketts, Thomas C.; Cuddeback, Gary; Burns, Barbara J.; Morrissey, Joseph
BACKGROUND: A number of states have implemented Assertive Community Treatment (ACT) teams statewide. The extent to which team-based care in ACT programs substitutes or complements primary care and other types of health services is relatively unknown outside of clinical trials.OBJECTIVE: To analyze whether investments in ACT yield savings in primary care and other outpatient health services.DESIGN: Patterns of medical and mental health service use and costs were examined using Medicaid claims files from 2000 to 2002 in North Carolina. Two-part models and negative binomial models compared individuals on ACT ( n = 1, 065 distinct individuals) with two control groups of Medicaid enrollees with severe mental illness not receiving ACT services ( n = 1, 426 and n = 41, 717 distinct individuals).RESULTS: We found no evidence that ACT affected utilization of other outpatient health services or primary care; however, ACT was associated with a decrease in other outpatient health expenditures (excluding ACT) through a reduction in the intensity with which these services were used. Consistent with prior literature, ACT also decreased the likelihood of emergency room visits and inpatient psychiatric stays.CONCLUSIONS: Given the increasing emphasis and efforts toward integrating physical health and behavioral health care, it is likely that ACT will continue to be challenged to meet the physical health needs of its consumers. To improve primary care receipt, this may mean a departure from traditional staffing patterns (e.g., the addition of a primary care doctor and nurse) and expansion of the direct services ACT provides to incorporate physical health treatments.